Implementasi Geogebra Pada Materi Bangun Ruang Sisi Lengkung Untuk Meningkatkan Hasil Belajar Matematik Siswa SMP - Yandi Aryanto; Cahya Cahya; Wahyu Setiawan (Departement of Mathematics Education, 2019)
This study aims to determine whether there is an increase in mathematical learning outcomes of junior high school students in Bogor district. In this study the population and sample are Arroyan Tanjungsari Middle School, Bogor Regency. The data of this study the authors provide tests in the form of pretest and posttest on the sample. The results of the research on the material of the curved side space that were carried out in accordance with the test results data were that learning based on geogebra applications clearly experienced an increase in mathematics learning outcomes in Bogor District Junior High School.